Level of knowledge of prevention of hepatitis C virus infection among nursing students - Sierpińska, Lidia; Kuleta, Edyta (Journal of Education, Health and Sport, 2020)
Introduction. Infection with hepatitis C virus (HCV) may lead to the severe form of chronic hepatitis C. According to the relevant literature, the percentage of infected population worldwide is approximately 2-3%, while in Poland it is about 1.4%. The incidence of hepatitis C is showing an upward tendency. The routes of infection with HCV are mainly associated with the disruption of tissue continuity, contact with infected blood, and via contact with infected medical equipment. The prevention of HCV infection in medical facilities is conditioned by non-specific prophylaxis, the essence of which is the cutting-off of transmission routes. Objective. The aim of the study was assessment of the level of knowledge concerning prevention of infection with hepatitis C virus among students of nursing at the Higher School in Radom. Material and Methods. The study was conducted in the first half of 2018, among 141 licentiate students of nursing at the Higher School in Radom. The research method was a diagnostic survey using a questionnaire technique. Results. The majority of respondents (98.6%) indicated the correct answer and reported that HCV is the ‘hepatitis C virus’. A large group of the examined students (94.3%) knew that ‘contact with infected blood’ may be the source of infection with HCV. The vast majority of respondents (87.9%) reported that infection with HCV may take place ‘for example, during a visit to a hairdresser or beautician, when there occurs damage to the skin’. The majority of adolescents (86.5%) knew that ‘everyone’ is exposed to HCV infection. More than a half of the students in the study (56.0%) knew that approximately 700,000 people in Poland are infected with HCV. In the opinions of the majority of respondents (88.7%) the best diagnostic method in infection with hepatitis C virus is ‘blood test for anti-HCV antibodies’. The largest number of students (61.0%) knew that there is no vaccine against hepatitis C, because the efforts to develop this vaccine have failed due to the high variability of the virus. A small group of the examined students (39.0%) had knowledge concerning the possibilities of curing a patient infected with HCV, as long as the disease is diagnosed early. The collected research material was statistically analyzed using the software StatSoft Statistica 13.1 PL and Microsoft Office software package. Non-parametric Pearson’s chi-squared test was used. The p values p<0.05 were considered statistically significant. Conclusions. The examined students had a high level of knowledge concerning the essence and situations of risk of infection with HCV. Students at the specialty of nursing should be motivated to expand their knowledge pertaining to prophylaxis of infection with hepatitis C virus. The risk of infection with HCV associated with occupational exposure should be considered while educating students of the specialty of nursing.